A Financial Overview in Real Estate Sector in Turkey: Optimization of the Leverage in Real Estate Development - ALNEHLAWI, SAAD (İstanbul Kültür Üniversitesi, 2024)
This thesis explores the financial feasibility of a residential real estate development project in Bahçeşehir, Istanbul. The project involves developing a residential complex on a 10,497.23 square meter plot with a construction area of 45,633 square meters. The primary research question (RQ) is: "What is the optimal financial leverage ratio that maximizes the project's profitability and financial performance under varying interest rate scenarios?" This study examines different equity and debt financing combinations, analyzing their impact on Net Present Value (NPV), Internal Rate of Return (IRR), and Return on Investment (ROI). The methodology includes a financial model with revenue projections, cost structures, and cash flow analysis, evaluating interest rate scenarios of 10%, 7%, 5%, and 2% to determine the optimal leverage ratio. The findings provide valuable insights for investors and developers, highlighting strategies to enhance project viability and profitability through effective leverage optimization.
Türkiye Gayrimenkul Sektörüne Finansal Bakış: Gayrimenkul Geliştirmede Kaldıracın Optimizasyonu
Yüksek lisans tezi.
Keywords: Financial Leverage; Real Estate Development; IRR; ROI; Strategic Financing